Progress Toward Polio Eradication — Somalia, 1998–2013 - Mbaeyi, Chukwuma (J Infect Dis, 2014)
Since the 1988 resolution of the World Health Assembly to eradicate polio, significant progress has been made toward achieving this goal, with the result that only Afghanistan, Nigeria, and Pakistan have never successfully interrupted endemic transmission of wild poliovirus. However, one of the greatest challenges of the Global Polio Eradication Initiative has been that of maintaining the polio-free status of countries in unstable regions with weak healthcare infrastructure, a challenge exemplified by Somalia, a country in the Horn of Africa region. Somalia interrupted indigenous transmission of wild poliovirus in 2002, four years after establishing its national polio eradication programme. But political instability and protracted armed conflict, with significant disruption of the healthcare system, left the country vulnerable to two subsequent imported outbreaks of wild poliovirus. The first occurred during 2005–2007, resulting in over 200 cases of paralytic polio, while the second importation in 2013 is currently ongoing. Despite immense challenges, the country has a sensitive surveillance system that has facilitated prompt detection of outbreaks, but its weak routine immunization system means that supplementary immunization activities constitute the primary strategy for reaching children with polio vaccines. Conducting vaccination campaigns in a setting of conflict has been at times hazardous but the country’s polio programme has demonstrated resilience in overcoming many obstacles to ensure that children receive life-saving polio vaccines. Regaining and maintaining Somalia’s polio-free status will, however, depend on finding innovative and lasting solutions to the challenge of administering vaccines in a setting of ongoing conflict and instability.